A Computational Approach towards the Development of Newer Anticancer Agents - Javed I. Sheikh; H. D. Juneja; V. N. Ingle (E-Journal of Chemistry)
In silico molecular docking analyses of the novel 1-(2', 4'-dihydroxy-5'-chlorophenyl)-3-aryl-propane-1, 3-diones were performed in the active sites of enzyme cytochrome P450 reductase to obtain new anticancer agents computationally. 1-(2', 4'-dihydroxy-5'-chlorophenyl)-3-(4"-methoxy-phenyl)-propane-1, 3-dione (3f) was found to have maximum affinity for the active sites of enzyme.